Through Sensus Fidelium to Deification: Listening to the Voice of the Faithful in Eastern Orthodoxy. (4th September 2018) - Maican, Petre
Abstract: The most significant challenge facing Eastern Orthodoxy is the laity's lack of engagement with their faith. In this article, I argue that this issue can be overcome by reintroducing the practice of consulting the laity in matters of faith ( sensus fidelium ). I begin by focusing on the benefits of sensus fidelium, as developed by Roman Catholic theology. I then move to demonstrate that sensus fidelium is also part of the Eastern Orthodox heritage. In the third section, I show the main risk the implementation of sensus fidelium raises, namely, confiscation by ultraconservative groups. Finally, I deal with this risk in the last section by placing the criteria for discerning the authentic voice of the laity in relation to the doctrine of deification.